Anticoccidial effects of Tinospora rumphii extract in naturally infected goats - Saladino, Pearl Muyco; Gonzaga, Elsa Amarille; Gonzaga, Loveille Jun Amarille (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: This study aimed to determine the anticoccidial potential of Tinospora rumphii ethanolic stem extract, resulting in an effective reduction in oocysts per gram counts of Eimeria species in goats in comparison to the commercial coccidiostat toltrazuril. Materials and Methods: Eighteen goats that were naturally infected with coccidia were identified as experimental animals. The experimental animals were grouped and were administered a single dose of T. rumphii extract at concentrations of 300, 600, 1,000, and 2,000 mg extract/kg body weight. The fecal samples were collected before treatment, during the first treatment, and every week thereafter for 28 days posttreatment. Fecal examination was carried out using a modified McMaster technique to determine the oocysts per gram of feces, and the mean efficacies of the extracts were calculated. Results: Stem extracts of T. rumphii were able to lower the oocysts per gram count than pretreatment for all concentrations, but the efficacy, in general, was still lower than toltrazuril. A significant difference existed in the efficacy of the extracts among the treatments on day 14. Administering 1,000 mg/kg extract resulted in the highest efficacy rate (95.25%) at 14 days posttreatment and was comparable to that of toltrazuril (89.89%). Conclusion: The results show that the T. rumphii stem extract has the potential to reduce the Eimeria species oocysts per gram counts of naturally infected goats. J. Adv. Vet. Anim. Res., 9(1): 8–12, March 2022 http://doi.org/10.5455/javar.2022.i563